Children Energy Expenditure by Doubly Labeled Water: Comparison of Multi-Point and Two-Point Methods - K Djafarian; JR Speakman; DM Jackson (Tehran University of Medical Sciences, 2005)
Objective: This study was designed to compare the multi-sample and two-sample methods in measuring children energy expenditure using doubly labeled water (DLW). Methods: Twenty-six healthy children (11 boys, 15girls; age 2-6 years) were recruited. The subjects in this study were from a subset of 90 children aged 2-6 years who were part of a larger study (RASCAL). After collection of a baseline urinary sample, every child was orally dosed with DLW based on body weight. Three urinary samples were taken at approximately 2, 4 and 6 hours after the isotope administration to determine the isotope dilution space and initial isotope enrichment. Further samples were collected, thereafter daily, preferably in the evening, for the next 14 days. Total energy expenditure (TEE) was measured over 7 and 14 days using the multi-point and two-point methods under free-living conditions by doubly labeled water. Results: There was no significant difference (T-test=0.79, P=0.439) between Total Energy Expenditure analyzed by the multipoint and two-point methods. There was also no significant difference between 7 and 14 days measurement of TEE using DLW. Conclusion: These data indicated that using 7 days measurement and two points method for measuring TEE in children is valid and cost-effective.